Human organoids are superior to cell culture models for intestinal barrier research - Kollmann, Catherine; Buerkert, Hannah; Meir, Michael; Richter, Konstantin; Kretzschmar, Kai; Flemming, Sven; Kelm, Matthias; Germer, Christoph-Thomas; Otto, Christoph; Burkard, Natalie; Schlegel, Nicolas (Frontiers in Cell and Developmental Biology, 2023)
Loss of intestinal epithelial barrier function is a hallmark in digestive tract inflammation. The detailed mechanisms remain unclear due to the lack of suitable cell-based models in barrier research.Here we performed a detailed functional characterization of human intestinal organoid cultures under different conditions with the aim to suggest an optimized ex-vivo model to further analyse inflammation-induced intestinal epithelial barrier dysfunction. Differentiated Caco2 cells as a traditional model for intestinal epithelial barrier research displayed mature barrier functions which were reduced after challenge with cytomix (TNFα, IFN-γ, IL-1ß) to mimic inflammatory conditions. Human intestinal organoids grown in culture medium were highly proliferative, displayed high levels of LGR5 with overall low rates of intercellular adhesion and immature barrier function resembling conditions usually found in intestinal crypts. WNT-depletion resulted in the differentiation of intestinal organoids with reduced LGR5 levels and upregulation of markers representing the presence of all cell types present along the crypt-villus axis. This was paralleled by barrier maturation with junctional proteins regularly distributed at the cell borders. Application of cytomix in immature human intestinal organoid cultures resulted in reduced barrier function that was accompanied with cell fragmentation, cell death and overall loss of junctional proteins, demonstrating a high susceptibility of the organoid culture to inflammatory stimuli. In differentiated organoid cultures, cytomix induced a hierarchical sequence of changes beginning with loss of cell adhesion, redistribution of junctional proteins from the cell border, protein degradation which was accompanied by loss of epithelial barrier function. Cell viability was observed to decrease with time but was preserved when initial barrier changes were evident. In summary, differentiated intestinal organoid cultures represent an optimized human ex-vivo model which allows a comprehensive reflection to the situation observed in patients with intestinal inflammation. Our data suggest a hierarchical sequence of inflammation-induced intestinal barrier dysfunction starting with loss of intercellular adhesion, followed by redistribution and loss of junctional proteins resulting in reduced barrier function with consecutive epithelial death.